Developing animals : wildlife and early American photography - Brower, Matthew (University of Minnesota Press, 2011)
Pictures of animals are now ubiquitous, but the ability to capture animals on film was a significant challenge in the early era of photography. This book takes us back to the time when Americans started taking pictures of the animal kingdom, at the beginning of the twentieth century, the moment when photography became a mass medium and wildlife photography an increasingly popular genre. The book investigates the way photography changed our perception of animals.